Factors Affecting For the Deposit Mobilization in Nepalese Commercial Banks - Shrestha, Swastika (Nepalese Journal of Finance, 2025)
This study examines the factors affecting for the deposit mobilization in Nepalese commercial banks. Return on assets and return on equity are the dependable variables. The selected independent variables are bank size, capital adequacy ratio, credit to deposit ratio, loan loss provision, non-performing loan. The study is based on data of 19 Nepalese commercial banks for the period from 2016/17 to 2021/22. Secondary data are used to extract the information from factors affecting for the deposit mobilization in Nepalese commercial banks. The regression models are estimated to test the significance and importance of factors affecting for the deposit mobilization in Nepalese commercial banks. The study showed that there are negative impact of non-performing loan and capital adequacy ratio on return on equity. It indicates that increase in non-performing loan and capital adequacy ratio leads to decrease in return on equity. Similarly, there are positive impact of non-performing loan and capital adequacy ratio on return on assets. It indicates that increase in non-performing loan and capital adequacy ratio leads to increase in return on assets. The result shows that there is a positive impact of credit to deposit ratio on return on assets and return on equity. It indicates that increase in credit to deposit ratio leads to increase in return on assets and return on equity. Likewise, loan loss provision and bank size have a positive impact on return on equity. It indicates that increase in loan loss provision and bank size leads to increase in return on equity. Similarly, loan loss provision and bank size have a negative impact on return on assets. It indicates that increase in loan loss provision and bank size leads to decrease in return on assets.